2014
DOI: 10.1007/s12663-014-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Calcifying Odontogenic Cyst: A Rare Entity

Abstract: The calcifying odontogenic cyst (COC) accounts for 1 % of jaw cysts, found most commonly as central lesion. The COC usually manifests itself as a painless, slow growing swelling, anterior to the first molar region. Radiographically it appears as a well-defined, unilocular radiolucency, and may have a radiopaque mass in its center. Majority of the cases appear before the fourth decade of life. The COC is found rarely in patients in the first decade of life. Histopathological features include a cystic lining dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In the present review of the literature on COC, DGCT, and GCOC, many publications did not describe full radiographic findings. It is true that radiological features, although suggestive, do not define the diagnosis of COC and DGCT . However, for future case reports, a better description of the radiographic findings is encouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present review of the literature on COC, DGCT, and GCOC, many publications did not describe full radiographic findings. It is true that radiological features, although suggestive, do not define the diagnosis of COC and DGCT . However, for future case reports, a better description of the radiographic findings is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that radiological features, although suggestive, do not define the diagnosis of COC and DGCT. [31][32][33][34] However, for future case reports, a better description of the radiographic findings is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the noticed various distribution Immunohistochemical Expression of Cortactin, E-Cadherin, and MDM2 Proteins in Solid Ameloblastoma (313) form for cortactin in ameloblastoma epithelial and stromal cells could reflect the various steps of actin turnover. It was found that although SAB and OKC exhibit slow growth; however, they have local invasive manners and high rate of recurrence if not treated with more aggressive actions (27,(34)(35)(36) .…”
Section: Discussionmentioning
confidence: 99%
“…There are cases of COC discovered during the avulsion of mandibular wisdom teeth after histological analysis of the pseudofollicular sac [2]. COC can be found in patients of all ages, equally in young children, adolescents, and adults [2,3].…”
Section: Discussionmentioning
confidence: 99%